The Approach to Processing of Biomedical Experimental Results - Sipaviciene, S. (Elektronika ir Elektrotechnika, 2012)
The aim is to analyze possibilities to approximate the signal of muscle reaction to stimuli using analytical functions, and to calculate required parameters Pt, CT and RT. It was shown, that under impact of one-time stimulus pulse it is purposeful to use sixth order polynomial for approximation. Polynomial coefficients with no less than 16 decimal places should be used for calculations. Algorithm for calculation of parameters Pt, CT and RT was presented. It was shown, that in case of muscle stimulation using complex signal it is more advisable to use reaction signal envelope detection methods. Experimental and calculation results are presented. Ill. 7, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1817